PENGUATAN KESEHATAN MENTAL KOMUNITAS DALAM MENCEGAH KEKERASAN SEKSUAL DI DESA MANGUNJAYA - Luthfi Ananda Putri; Lucky Purwantini; Siti Nurhidayah (Universitas Islam 45 Bekasi, 2022)
Learning healthy internet ethics is one of the lessons that needs to be delivered from an early age so that internet users can use and use the internet in a healthy and safe manner. Lack of parental control over their children when accessing the internet in the environment where these activities are carried out. This needs to be conveyed to increase awareness of the internet world and the ability to sort out the content that is accessed, it is necessary to have an understanding of the importance of healthy and safe internet usage. Sexual violence can occur in children and adolescents, because they are considered as someone who is weak and has a high dependence on the adults around them. Sexual violence in dating in the results of the data obtained often occurs in adolescents aged from 15 years. Therefore, the authors hold psychoeducational activities about healthy internet and self-control training for teenagers about healthy internet using the webinar (zoom meeting) method, KSDP Psychoeducation (Sexual Violence in Dating) for teenagers using whatsapp group media and making physical media in the form of posters and videos. uploaded via social media Tiktok with Action Stop Sexual Violence against Women and Children.